Hak Asasi Manusia: Pendidikan sebagai sarana penanaman kesadaran hak asasi manusia dan implementasi hak atas pendidikan - Rahmawati, Febby Indah (Maliki Interdisciplinary Journal, 2026)
This study analyzes the relationship between education and Human Rights (HR) within the Indonesian legal system. The primary issue in fulfilling the right to education is the presence of significant disparities on the ground, such as quality gaps, economic and geographical factors, as well as discrimination against children with disabilities, indigenous groups, and children in remote or 3T (frontier, outermost, and remote) areas. Normatively, this right is firmly guaranteed under Article 31 of the 1945 Constitution and the National Education System Law. As a solution, this article proposes an integrative approach through human rights education implemented within curricula like the Merdeka Curriculum, alongside strengthening the role of teachers as human rights agents to foster a young generation that is adaptive, critical, and appreciative of diversity. The research concludes that the realization of a just right to education does not rely solely on formal regulations. This right can only be optimally achieved if supported by the implementation of human rights education that is experience-based, dialogic, and critical, as well as sustained by consistent government policies.